Analysis of the foreign direct investment: the case of Portugal - Rolo, Maria Nunes Moreira Cabral (2018)
This dissertation analyses the evolution of the Global FDI, with emphasis on Portugal. Firstly, it is made a theoretical approach on FDI, and then it is analysed the data related with Global FDI and Portugal FDI. The choice of topic for the master thesis results from its relevance for the economies of the world and specifically for the Portuguese economy. In Portugal, the FDI constitutes a priority for Portuguese Government. Indeed, this source of financing is an alternative to bank loans, which present high interest rates, even more when uncertainty arises, as a result of the 2008 economic and financial crisis experienced worldwide and more particularly in Portugal. For that reasons, it becomes essential to understand how the crisis affected FDI in Portugal, which determinants attract investors to Portugal, as what policies and incentives have already been implemented by the Portuguese Government in order to capture more FDI and what still needs to be done in order to improve this investment. As conclusive points, it is possible to highlight: (1) Globally, the effects of the crisis were only felt in FDI in 2008, and were only able to recover in 2010. (2) In the case of Portugal, the inflows decline in 2007, recovering in the following year. As for the outflows, the impact of the crisis was also felt in 2007, but the recovering occurred only in 2011. (3) There are still issues that need to be addressed in order to attract more FDI, namely in terms of taxes, bureaucracy and policy measures.